1999
DOI: 10.1046/j.1439-0329.1999.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoplastic and total peroxidase activities in Scots pine needles at subarctic polluted sites

Abstract: A gradient survey was carried out in order to compare peroxidase activity in Scots pine (Pinus sylvestris) needles in relation to distance from the industrial centre of Monchegorsk, on the Kola Peninsula in north-western Russia. Apoplastic and total peroxidase activity and sulphur (S), nickel (Ni) and copper (Cu) content in the needles of mature trees were measured on seven plots located between 10 and 110 km from the pollution source. Peroxidase activities in both current-and previous-year needles increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…Calzada et al (2001) showed that the peroxidase activity of Pinus radiata was generally higher in June than in September in a rural-forested area of northern Spain. At subarctic polluted sites, total peroxidase activity of Pinus sylvestris from an industrial center of Monchegorsk in northwestern Russia showed a clear relationship to the pollution gradient in winter compared to autumn (Roitto et al 1999). However, peroxidase activities of Ficus microcarpa did not show any significantly seasonal variation in the present study, whereas superoxide dismutase activities of Ficus microcarpa were usually the lowest during winter.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Calzada et al (2001) showed that the peroxidase activity of Pinus radiata was generally higher in June than in September in a rural-forested area of northern Spain. At subarctic polluted sites, total peroxidase activity of Pinus sylvestris from an industrial center of Monchegorsk in northwestern Russia showed a clear relationship to the pollution gradient in winter compared to autumn (Roitto et al 1999). However, peroxidase activities of Ficus microcarpa did not show any significantly seasonal variation in the present study, whereas superoxide dismutase activities of Ficus microcarpa were usually the lowest during winter.…”
Section: Discussioncontrasting
confidence: 78%
“…In fact, high peroxidase activity observed in this study cannot be attributed to ozone pollution alone in each study site. Several researchers have suggested that peroxidase activity may not be used as a specific indicator of single air pollutant and can only be considered as a general indicator of oxidative stress (Nyman 1986;Roitto et al 1999). Moreover, oxidation products generated from free radial reactions, such as aldehydes, have been suggested as useful biomarkers of O 3 exposure (Pryor et al 1996) or NO 2 exposure (Robison et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…To obtain specific POD activity per protein content, the standard Bicinchoninic Acid assay (Roitto, Ahonen-Jonnarth, Lamppu, & Huttunen, 1999) was used for protein determination with bovine serum albumin as a standard.…”
Section: Seedling Performancementioning
confidence: 99%